Effect of Boiling, Steaming, and Autoclaving Methods on the Physical Characteristics of Moringa (Moringa oleifera) Seed Flour - Salman, Annisa Nazifa; Gunawan, Chandra; Ristia, Jeany; Panjaitan, Bintang Sipartogi (Journal of Engineering Science and Technology Management (JES-TM), 2025)
This study evaluated the effect of moist heat processing (boiling, steaming, autoclaving) on the physical properties of Moringa oleifera seed flour to determine the optimal pretreatment for product development. Exotesta of moringa seeds were removed, subjected to the treatments, oven-dried, grounded, and sieved (60 mesh). Moisture content, color (CIELab), bulk density, and angle of repose were analyzed. Results showed that all treatments increased moisture content compared to raw seeds (4,36–4,46%), with no significant difference among treatments. Autoclaving produced flour with the highest bulk density (0,4258 g/cm³) and lowest angle of repose (33,37°), indicating better flowability. Color analysis revealed darker flour in autoclaved and boiled samples due to Maillard reactions. Overall, autoclaving is the most effective pretreatment for producing denser, free-flowing Moringa seed flour suitable for functional food applications.